Developing and characterizing functionally enhanced plant proteins for food applications - Shen, Yanting (Kansas State University, 2021)
The demand for protein as food ingredient and in the human diet continues to increase due to its nutritional benefits, functional properties, rising protein deficiency, and the growing world population. Plant-based proteins represent a more sustainable source to supplement costly animal proteins. The goal of this study was to improve protein functional properties through different modification approaches, understand the physicochemical properties of the modified proteins, and evaluate their utilization in several food models. Specific objectives were to: 1) investigate the effect of different drying methods, namely freeze drying, spray drying, and vacuum drying on the functional and physicochemical properties of quinoa protein isolate; 2) improve the functional properties of pea protein through chemical and enzymatic modifications; 3) investigate the functional properties of pea protein by modulating protein covalent and non-covalent interactions and understand the physicochemical characteristics of the unfolded pea proteins that are responsible for the functional changes; and 4) evaluate the modified pea proteins as functional food ingredient in meat patty and egg-free mayonnaise applications. The freeze-dried quinoa protein had the highest emulsification capacity and stability and oil holding capacity (OHC), which was attributed to its higher surface hydrophobicity, while the spray-dried quinoa protein had the highest solubility at pH 7 and water holding capacity (WHC). Gels (8% protein in water, w/w) prepared with the freeze-dried protein had higher elastic and viscous modulus than that of the other drying methods. When comparing pea protein modification through acylation, conjugation, and sequential acylation/conjugation, the sequential modification method demonstrated more beneficial and synergistic effects and greatly enhanced the WHC, OHC, emulsification and gelation properties of pea protein isolate (PPI). The enzyme or/ and conjugation modifications also enhanced the functional properties on pea protein, including increased WHC, OHC, emulsion capacity, emulsion stability, and gelation. The modified pea proteins had comparable sensory scores as the control pea protein, and these modifications overall did not negatively affect protein sensory properties. For the protein interaction study, both urea and SDS unfolded proteins had significantly higher water holding capacity and oil holding capacity with up to 5.01 and 5.09 g H2O /g protein, and 3.06 and 2.84 g oil /g protein compared with the control pea protein (4.12 and 1.29 g), respectively. The proteins unfolded with urea or SDS also showed improved emulsification properties. The trypsin hydrolyzed protein exhibited the highest foaming capacity and better gelation properties among all the treatments. Principal component analysis indicated strong associations between protein functional and physicochemical properties and molecular interactions. The newly developed pea proteins produced through enzyme/polysaccharide conjugation modifications were successfully used applied in meat patties as functional extenders and in mayonnaise as an alternative to egg yolk. Beef patties containing the modified pea protein through sequential deamidation and conjugation (PGG, especially at 5%) showed significantly decreased cooking loss of only 20% and increased moisture and fat retentions compared with the control patty (33% cooking loss). In general, PPI patties exhibited harder texture (e.g., hardness, chewiness, shear force) than the control patty, while PGG patties showed much softer texture than the control. Emulsions prepared with guar gum conjugated PPI (G-PPI) had significantly increased stability, apparent viscosity, and decreased droplet size compared with the PPI emulsions. Several factors, including pH, NaCl concentration, protein concentration, and oil/water ratio significantly affected emulsifying properties of the modified pea protein. The mayonnaise with G-PPI at higher concentrations (6 and 8%) exhibited significantly higher emulsifying properties and viscoelasticity than that made of PPI or egg yolk. In conclusion, quinoa protein isolate with different functional properties can be obtained by using different processing methods. Functional properties of pea protein can be enhanced through manipulated modification of specific structural domains using different modifiers. The modified pea proteins demonstrated advantageous features when applied in meat patties and mayonnaise products. The modified proteins may also have potential applications in meat analogues, bakery products, and emulsified foods and beverages.
Keywords: Protein functional properties; Protein modification; Food application; Pea protein; Plant protein; Physicochemical properties